2017
DOI: 10.1002/zaac.201700060
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Properties of Lanthanide‐Organic Frameworks (LnOFs) with Thiophene‐2,5‐Dicarboxylate and Acetate

Abstract: S-heterocyclic dicarboxylic acid, thiophene-2,5-dicarboxylic acid (H 2 TDC), was employed to construct a series of lanthanideorganic frameworks (LnOFs) with coligand acetate, formulated as [Ln(TDC)(OAc)(H 2 O)] n [Ln = Eu (1), Tb (2), Gd (3), Dy (4), Sm (5)] under hydrothermal conditions. Structure analysis reveals that 1-5 have dinuclear 3D metal organic frameworks (MOFs), in which TDC 2and OAcdisplay (κ 1 -κ 1 )-(κ 1 -κ 1 )-μ 4 and (κ 2 -κ 1 )-μ 2 coordination fashions, respectively. The dehydrated products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Lanthanide (such as Tb and Eu) MOFs have been widely used in fluorescent probes because of their multiple coordination modes and brilliant fluorescence characteristic. , Many lanthanide MOFs were applied in detecting metal cations, inorganic anions, , and organic small molecules. However, it is rarely reported that Ln-MOF was devoted to detecting MG and UA. , Herein, we synthesized an Ln-MOF Eu 2 (TDA) 4 ­(OOCCH 3 ) 2 ­(H 2 O) 2 (referred to as Eu-TDA, TDA = 2,5-thiophenedicarboxylic acid group, OOCCH 3 = glacial acetic acid group) and surveyed its applications in fluorescence sensor. The same crystal structures constructed by Eu and TDA have been reported, but their applications in fluorescence detection have not been explored. The luminescent explorations in our work revealed that Eu-TDA can rapidly detect malachite green and uric acid, possessing relatively high selectivity and sensitivity.…”
Section: Introductionmentioning
confidence: 94%
“…Lanthanide (such as Tb and Eu) MOFs have been widely used in fluorescent probes because of their multiple coordination modes and brilliant fluorescence characteristic. , Many lanthanide MOFs were applied in detecting metal cations, inorganic anions, , and organic small molecules. However, it is rarely reported that Ln-MOF was devoted to detecting MG and UA. , Herein, we synthesized an Ln-MOF Eu 2 (TDA) 4 ­(OOCCH 3 ) 2 ­(H 2 O) 2 (referred to as Eu-TDA, TDA = 2,5-thiophenedicarboxylic acid group, OOCCH 3 = glacial acetic acid group) and surveyed its applications in fluorescence sensor. The same crystal structures constructed by Eu and TDA have been reported, but their applications in fluorescence detection have not been explored. The luminescent explorations in our work revealed that Eu-TDA can rapidly detect malachite green and uric acid, possessing relatively high selectivity and sensitivity.…”
Section: Introductionmentioning
confidence: 94%
“…30 Each TDA ligand adopts a single μ 4 -(η 1 , η 1 )–(η 1 , η 1 ) bis-bidentate coordination mode connecting four lanthanide ions. 32 The Fourier transform infrared (FTIR) spectra of the ligands and BHP-MOFs are shown in Fig. S6 †.…”
Section: Resultsmentioning
confidence: 99%
“…1b-d) were obtained. [28][29][30][31][32] The isostructural BHP-MOFs were further studied in detail to demonstrate the aforementioned bimetallic strategy. 28,30,33 As shown in Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%